Event-triggered control for continuous-time switched systems - Xin Wang; Dan Ma (The 27th Chinese Control and Decision Conference (2015 CCDC), 2015)
The co-design problem of an event generator and a hybrid controller for continuous-time switched systems is investigated. By using the piecewise Lyapunov function method and the average dwell time approach, we prove the exponential stability of the system under a hybrid event-triggered controller. A sufficient condition on the existence of the hybrid control law and the event generator is established via linear matrix inequalities. Consequently, we propose that the inter-execution times have positive lower bound. Finally, an example is presented to illustrate the feasibility and efficiency of the proposed method.